Modeling surface pH measurements of oocytes. (1st July 2022) - Bocchinfuso, A; Calvetti, D; Somersalo, E
Abstract: The transport of gases across cell membranes plays a key role in many different cell functions, from cell respiration to pH control. Mathematical models play a central role in understanding the factors affecting gas transport through membranes, and are the tool needed for testing the novel hypothesis of the preferential crossing through specific gas channels. Since the surface pH of cell membrane is regulated by the transport of gases such as CO2 and NH3, inferring the membrane properties can be done indirectly from pH measurements. Numerical simulations based on recent models of the surface pH support the hypothesis that the presence of a measurement device, a liquid-membrane pH sensitive electrode on the cell surface may disturb locally the pH, leading to a systematic bias in the measured values. To take this phenomenon into account, it is necessary to equip the model with a description of the micro-environment created by the pH electrode. In this work we propose a novel, computationally lightweight numerical algorithm to simulate the surface pH data. The effect of different parameters of the model on the output are investigated through a series of numerical experiments with a physical interpretation.